Diamond-Based Solvated Electron Generators: A Perspective on Applications in NRR, CO2RR, and Pollutant Degradation - Mattia Cattelan (Solids, 2025)
The generation of solvated electrons (SEs) from solid-state sources represents a transformative approach to driving challenging reduction reactions under ambient conditions. Diamond, with its almost unique negative electron affinity (NEA) and tunable electronic properties, is emerging as a promising candidate for SE generation in aqueous media. This perspective article reviews the current state of diamond-based SE generators and discusses their potential to catalyze sustainable nitrogen reduction (NRR) to ammonia, carbon dioxide reduction (CO2RR), and the degradation of persistent environmental pollutants. Emphasis is placed on the fundamental processes enabling SE photoinjection from diamond to water, recent experimental breakthroughs, and the prospects for scalable, green applications.